Alat Pengusir Tikus Via SMS Berbasis Arduino - Clara Clara; Rio Aditya Dwi Pratama; Aisen Odnikana Setyanamurwan; Yoga Budi Bhakti (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2020)
The increasing of rat population in the environment around us, will cause anxiety, both due to mouse droppings that can be scattered everywhere even in corners of the room that are not visible to us, This will certainly make us very uncomfortable and will certainly cause various kinds of diseases because of the dirty environment.  the impact of rats is that can also cause household appliances such as clothes, cables, and other important items to be damaged due to the rat's act. This will certainly make us very uncomfortable, many of people try various ways may have been done to be able to completely eradicate these rats, but in reality, rats will never completely lost from our lives, we can only prevent these rats from entering our homes. Therefore, we try to assemble and create a tool that can repel or minimize the presence of rats in the house, by utilizing technology. The modern technology that we convey here is Short Message technology or SMS. SMS here is used to inform us about the presence of mice that may intend to enter the house. This of course will make it very easy for device users if they are away from home.